Dual crosslinked carboxymethyl cellulose/polyacrylamide interpenetrating hydrogels with highly enhanced mechanical strength and superabsorbent properties. (15th March 2020) - Jeong, Daham; Kim, Chulgu; Kim, Yohan; Jung, Seunho
Graphical abstract: Highlights: CMC/PAM IPN hydrogels were prepared by a sequential dual crosslinking strategy. Tensile length of CMC/PAM-1 IPN hydrogels were up 2.6 time higher than CMC gel. Compressive strength of CMC/PAM-1 IPN hydrogels were up 4.5 time higher than CMC gel. The CMC/PAM-1 IPN hydrogels has higher superabsorbent properties than CMC gel. The CMC/PAM IPN hydrogel has non-cytotoxicity on animal cells. Abstract: Carboxymethyl cellulose (CMC)-based hydrogels possess superabsorbent properties and are biocompatible; however, their use is limited because of their low mechanical strength. In the present study, we used a sequential dual crosslinking strategy to produce new CMC-based interpenetrating polymer network (IPN) hydrogels with high mechanical strength and superabsorbent properties. The newly synthesized CMC-based IPN hydrogels were first crosslinked with CMC using ethylene glycol diglycidyl ether (EGDE) under basic conditions and were then subjected to secondary radical polymerization by adding acrylamide, N, N ′-methylene bis-acrylamide (MBA), and ammonium peroxodisulfate. The structure and morphologies of the CMC with polyacrylamide (PAM) IPN hydrogels were characterized by Fourier transform infrared spectroscopy in the attenuated total reflectance mode (FTIR-ATR), solid-state nuclear magnetic resonance (NMR) spectroscopy, thermogravimetric analysis (TGA), field emission scanning electron microscopy (FE-SEM), rheology analysis, tensile test, and compressive test. The synthesized CMC/PAM IPN hydrogels exhibited highly enhanced mechanical strength with high density internal structure due to the double crosslinking of CMC and PAM. The tensile length and compressive strengths of CMC/PAM-1 IPN hydrogels were up to 2.6 and 4.5 times higher than that of the CMC gel, respectively. Moreover, CMC/PAM-1 IPN hydrogels presented higher superabsorbent properties than any other CMC-based IPN hydrogels reported so far. The present study proposes a novel method for the synthesis of CMC-based hydrogels that can simultaneously have very high mechanical strength as well as superabsorbency. These hydrogels do not show biotoxicity against in vitro animal cell and has the potential to be used as a biomaterial.